The impact of (more) enlargement on the European Employment Strategy - Ingham, Mike; Ingham, Hilary; Bıçak, Hasan Ali; Altınay, Mehmet (Industrial Relations Journal/Wiley, 2005)
ABSTRACT: The European Union (EU) aspires to be the most competitive, full employment economy in the world and has set a number of ambitious targets to be met by 2010 in order that it can achieve this goal. At the same time, it is pursuing an enlargement policy that will witness the accession of an increasing number of less developed nations. This article explores some of the tensions that exist between these two goals as these are manifest in labour market indicators and finds the likelihood of meeting the deadline set for success remote
Keywords: European; Employment Strategy